DK complete sailing manual - Sleight, Steve (DK Penguin Random House, 2017)
The ultimate illustrated guide for sailors is now fully revised and updated. With a foreword by Olympic gold medallist Sir Ben Ainslie, and covering the latest developments in sailing and navigation technology, this manual is the undisputed market leader in sailing guides. The Complete Sailing Manual now offers even more extensive coverage of sailing practice, including foiling catamarans, apparent wind sailing, long-distance cruising, and electronic navigation. Former British national champion Steve Sleight offers a complete tuition course on seamanship, and his expert advice is brought to life with breathtaking action photography